Impact of Rice Husk, Banana Peel and Egg Shell as Biodegradable Adsorbent for Heavy Metal Treatment of Industrial Wastewater - Chandra, Satish Singh; Masroor, Mohammad Danish; Nayeem, MD Rashid; Masrror, Zakkia (International Journal of Aquatic Research and Environmental Studies, 2026)
Industrialization causes pollution of the environment around globe. This contamination is a problem because the water gets contaminated with harmful metals. Heavy metals are becoming source of contaminating the ocean, soil, factories, and even cleaned waste water. These metals are being released into the environment, both naturally and artificially. The release of industrial waste into water can harm plants and animals in the water and can also make people sick. This is a major problem around the globe because the waste is poisonous and can cause serious harm. Non-biodegradable items cannot break down naturally, so if they end up in an ecosystem, they negatively affect the environment. That's why it's important to find new ways to remove heavy metals from pollution sources before they harm the environment by an environmentally biodegradable material. Now adays, there are various ways to filter waste water of industries containing heavy metals [6]. These methods include precipitation, reverse osmosis, activated sludge process, and adsorption [16, 18, 19, 21]. Some scientists used soil for treatment the industrial waste water as well [8, 16]. In recent years, the Adsorption method has been considered as a top choice for removing heavy metals from industrial waste. It works just as well as traditional methods. Therefore, authors used biodegradable solution to the problem using rice husk, banana peel and egg shell. This study explores how rice husk, banana peels and egg shells can be used effectively as eco-friendly biodegradable adsorbents. Rice husk, banana peels and egg shells were used to create a natural and environmentally friendly biodegradable material that can remove impurities from water solutions. Rice husk, banana peels and egg shells are easily found waste products that were selected for this purpose. Rice husk, banana peels and egg shells were cleaned, dried, and crushed to very small sizes orderly in 100-150 µm and 200 µm. These small particles were then used to treat pharmaceutical waste water. All three selected substances were combined and used to clean dirty water with different amounts, different pH levels, and different amounts of time. The authors used the batch method to understand how adsorption works. The test was done in two different situations including one where things were steady and one where things were moving.
Keywords: Biodegradable, Bio-adsorbent, Banana Peel, Egg shell, Rice Husk, Wastewater Treatment.